2015
DOI: 10.1007/s10980-015-0238-9
|View full text |Cite
|
Sign up to set email alerts
|

Termite mounds mitigate against 50 years of herbivore-induced reduction of functional diversity of savanna woody plants

Abstract: Context Spatially heterogeneous habitats often promote woody plant species and functional diversity (FD). Ungulate herbivory can have the opposite effect. Across the globe, the type and intensity of herbivory is changing, as domestic livestock replace wild ungulates, which are increasingly confined to protected areas. Despite recognition of the importance of FD for ecosystem functioning, the interactive effect of soilrelated fine-scale heterogeneity and larger-scale ungulate herbivory on woody plant FD is litt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 67 publications
1
14
0
Order By: Relevance
“…As abundances of species outside the mounds were not examined, we are unable to comment on the preference of termite mounds as nesting sites compared with other microhabitats. However, this study supports previous work that has found termite mounds act as refuges for a range of animals (Choosai, Mathieu, Hanboonsong, & Jouquet, 2009;Joseph et al, 2015;Joseph, Seymour, Cumming, Mahlangu, & Cumming, 2013).…”
Section: Introductionsupporting
confidence: 91%
“…As abundances of species outside the mounds were not examined, we are unable to comment on the preference of termite mounds as nesting sites compared with other microhabitats. However, this study supports previous work that has found termite mounds act as refuges for a range of animals (Choosai, Mathieu, Hanboonsong, & Jouquet, 2009;Joseph et al, 2015;Joseph, Seymour, Cumming, Mahlangu, & Cumming, 2013).…”
Section: Introductionsupporting
confidence: 91%
“…Slower decomposition in encroached areas has important implications for the global carbon budget, given the importance of decomposition to global carbon fluxes (Raich & Schlesinger, 1992), as well as for nutrient cycling in these systems. The reduction in termite activity in encroached areas also has important implications for multiple other ecosystem processes since termites are keystone organisms that influence several attributes of savanna ecosystems, including soil properties, hydrology, vegetation communities and the patterns and impacts of herbivory (Davies et al, 2016;Joseph et al, 2015;Sileshi, Arshad, Konate, & Nkunika, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in many habitats (e.g., miombo), termite mounds harbor evergreen vegetation (Joseph et al. , ), whereas the surrounding matrix is dominated by deciduous species, so mounds represent year‐round patches of shade. Finally, variation explained by random effects indicates that site and time of day of measurement had some influence on Δ T , because random effects increased variance explained by 5%.…”
Section: Discussionmentioning
confidence: 99%